Histone deacetylases in virus‐associated cancers. (19th November 2019) - Mirzaei, Habibollah; Ghorbani, Saeed; Khanizadeh, Sayyad; Namdari, Haideh; Faghihloo, Ebrahim; Akbari, Abolfazl
Summary: Oncogenic viruses are one of the most important causes of cancer worldwide. The pathogens contribute to the establishment of human malignancies by affecting various cellular events. Epigenetic mechanisms, such as histone modification methylation/demethylation, are one of the most critical events manipulated by oncogenic viruses to drive tumorigenesis. Histone modifications are mediated by histone acetylation and deacetylation, regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs), respectively. Dysregulation of HDACs activity affects viral tumorigenesis in several ways, such as manipulating tumor suppressor and viral gene expression. The present review aims to describe the vital interactions between both cancer‐caused/associated viruses and the HDAC machinery, particularly by focusing on those viruses involved in gastrointestinal tumors, as some of the most common viral‐mediated cancers.